Large mid-latitude stratospheric temperature variability caused by inertial instability: A potential source of bias for gravity wave climatologies - Rapp, Markus; Dörnbrack, Andreas; Preusse, Peter (Geophysical Research Letters, 2018)
Stratospheric temperature perturbations (TP) that have previousl y been misinterpreted as du e to gravity waves are revisited . The perturbations ob-served by radio occultations during December 2015 had peak-to-peak amplitudes of 10 K extending from t h e Equator to mid-latitud es. The vertically stacked and horizontally flat structures had a vertical wavelength of 12 km.The signs of the TP were 18 0◦ phase shi ft ed between equat o r i al and midlatitudes at fi xed altit u d e levels. High-resolutio n operational analyses reveal that th ese shallow temperature structures were caused by inertial instabil- ity (II) due to the large meridional shear of the polar night jet (PNJ) at ist equatorward flank in combination with Rossby wave breaking. Large stratospheric TP owing to II do frequently occur in th e Northern Hemisphere (South- ern Hemisp h er e) from October to Apri l (April to October) in the 39 years of ERA-Interim data. During 10% of the days, TP exceed 5 K (peak-to -peak) .